(untitled) (Journal of Engineering, 2010)
The ECG is used for the clinical analysis of physiological data has occurred in the field of cardiology. Certain abnormalities of the ECG are quite well defined and can be readily identified. The digital signal processing Slantlet Transform is used in the feature extraction of ECG monitoring and Diagnosis system to convert the continuous ECG signal to a form can be classified by a classifier of the ECG monitoring and Diagnosis system to detect the cardiac abnormalities.In this paper, FPGA is used to build the slantlet Transform of the ECG feature extraction VHDL program of FPGA is used in the work, the obtained output results are similar to the past work results, which is built by using Mat Lab program, in accuracy and closing to the original ECG signal. Using FPGA decreases the cost and time for building hardware system of ECG Monitoring and Diagnosis system. It also gives more flexibility than the alternate approaches. Mat-Lab program is used only for displaying the input and output discrete signals of slantlet transform